SMART PRINTING LABS: AI-ENABLED MANAGEMENT SYSTEMS - Saraswat, Vivek; Singh, Mahi; Sidhu, Amritpal; Faisal, Mohd; Upadhyay, Satish; S. Murugan; Savant, Ila Shridhar (ShodhKosh: Journal of Visual and Performing Arts, 2025)
With the development of the printing technology toward automation and smartness, there is the emergence of Smart Printing Labs, areas that involve artificial intelligence (AI), Internet of Things (IoT), and cloud computing to form self-optimizing, data-driven production environments. The evidence in this paper is a framework of AI-Enhanced Smart Printing Lab that can improve operational efficiency and predictive maintenance and managerial decision-making via built-in sensing, analytics, and control. The suggested system uses machine learning algorithms (convolutional neural networks (CNN), long short-term memory (LSTM), and reinforcement learning (RL)) to plan the workflow, identify defects, and control the process in a real-time manner. Data collection and cloud data synchronization with IoT guarantee the constant control of print parameters, allowing to predict faults and maximize energy consumption. Experimental evidence shows throughput increase by 24 percent, reduction of downtimes by 36 percent and 18 percent decrease in energy and 50 percent cut in defect rates respectively as compared to conventional configurations. The study brings in a modular scalable architecture in line with the principles of Industry 4.0 and sustainable manufacturing. The future work aims to develop this system further with the help of federated AI models and cross-facility learning networks, which facilitate joint intelligence in the distributed industrial setting.